Best Answer

-6x + 0 = 45

Simplifies to:

-6x = 45.

By dividing both sides by -6, we arrive at the final:

x = -45/6

Q: If -6x plus 0 equals 45 then what is x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It is: 3x2+6x-11 = 0

From what i understand the equation is like this; (3 * 2 ) + 6x + 24 = 0 6 + 6x +24 = 0 6x = - 24 - 6 6x = - 30 x = - 5

2sin2(6x) + 3sin(6x) + 1 = 0 Solving the quadratic, sin(6x) = -1 or sin (6x) = -0.5 sin(6x) = -1 => 6x = 45+60n degrees for integer n sin(6x) = -0.5 => 6x = 35+60n or 55+60n degrees for integer n.

6x+5=3x+5 5=9x+5 x=0

2x2+6x-8 = 72 2x2+6x-8-72 = 0 2x2+6x-80 = 0 (2x-10)(x+8) = 0

Related questions

It is: 3x2+6x-11 = 0

From what i understand the equation is like this; (3 * 2 ) + 6x + 24 = 0 6 + 6x +24 = 0 6x = - 24 - 6 6x = - 30 x = - 5

7x + 2 = 6x + 2 if and only x = 0.

x2 + 6x + 8 = 0 Solve for x.X = -2 or X = -4

2sin2(6x) + 3sin(6x) + 1 = 0 Solving the quadratic, sin(6x) = -1 or sin (6x) = -0.5 sin(6x) = -1 => 6x = 45+60n degrees for integer n sin(6x) = -0.5 => 6x = 35+60n or 55+60n degrees for integer n.

x+15+(-15)=6x+(15+(-15)=6x+(15-15)=6x+(0)=6x+0=6Add/subtract 0 from both sides,x=6

6x+5=3x+5 5=9x+5 x=0

2x2+6x-8 = 72 2x2+6x-8-72 = 0 2x2+6x-80 = 0 (2x-10)(x+8) = 0

x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0

If: x+3+6x+9 = 0 then 7x+12 = 0 So: 7x = -12 and x = -12/7

the answer is -3x = 0

6x+2y-3 = 0 2y = -6x+3 y = -3x+3/2 in slope intercept form